Molecular Mechanism of Inhibition of Polysialyltransferase Domain (PSTD) by Heparin - Liao, Si-Ming; Liu, Xue-Hui; Peng, Li-Xing; Lu, Bo; Huang, Ri-Bo; Zhou, Guo-Ping (Current Topics in Medicinal Chemistry, 2021)
The polysialic acid (polySia) is a unique carbohydrate polymer produced on the surface of Neuronal Cell Adhesion Molecule (NCAM) in a number of cancer cells, and strongly correlates with the migration and invasion of tumor cells and with aggressive, metastatic disease and poor clinical prognosis in the clinic. Its synthesis is catalyzed by two polysialyltransferases (polySTs), ST8SiaIV (PST) and ST8SiaII (STX). Selective inhibition of polySTs, therefore, presents a therapeutic opportunity to inhibit tumor invasion and metastasis due to NCAM polysialylation. It has been proposed that NCAM polysialylation could be inhibited by two types of heparin inhibitors, low molecular heparin (LMWH) and heparin tetrasaccharide (DP4). This review summarizes how the interactions between Polysialyltransferase Domain (PSTD) in ST8SiaIV and CMP-Sia, and between the PSTD and polySia take place, and how these interactions are inhibited by LMWH and DP4. Our NMR studies indicate that LMWH is a more effective inhibitor than DP4 for inhibition of NCAM polysialylation. The NMR identification of heparin-binding sites in the PSTD may provide insight into the design of specific inhibitors of polysialylation.
Keywords: NMR